Measuring the sosial economic benefits of Jabres cattle keeping in Bantarkawung Sub-district, Brebes, Central Java, Indonesia - Haq, M. S.; Budisatria, I. G. S.; Panjono, P.; Maharani, D. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
This study aimed to explore the socio-economic benefits of Jabres cattle as potential local livestock in two agro ecological zones, lowlands and middle zone in Bantarkawung Sub-District, Brebes, Central Java. The data were collected by Participatory Rural Appraisal (PRA) method, which is an approach to families or individuals to analyze the reality of their living conditions. This study involved 60 farmers which selected by purposive sampling based on three considerations. The analytical model used to test differences is the analysis of independent T-test. The result showed that the farmers in the middle zone are younger and most of their cattle keeping motivation are for livelihood. Meanwhile, the farmers in the low lands are older and most of their cattle keeping motivation is for saving only (2.90±0.31). This condition caused the socio-economic benefit difference between those locations where the value of net production (185±27 kg/y), added value (IDR 4.900.000±1.204.000), and total benefits (IDR 9.289.000±1.542.000) were higher in the medium land than in the lowlands. Based on these reasons, it can be concluded that middle zone farmers have more possibility to sustain their farm than those of lowlands farmers.